Watermark Based on Singular Value Decomposition (Baghdad Science Journal, 2023)
Watermarking operation can be defined as a process of embedding special wanted and reversible information in important secure files to protect the ownership or information of the wanted cover file based on the proposed singular value decomposition (SVD) watermark. The proposed method for digital watermark has very huge domain for constructing final number and this mean protecting watermark from conflict. The cover file is the important image need to be protected. A hidden watermark is a unique number extracted from the cover file by performing proposed related and successive operations, starting by dividing the original image into four various parts with unequal size. Each part of these four treated as a separate matrix and applying SVD on it, the diagonal matrix is selected to determine its norm. The four norms will be processed to produce one unique number used as a watermark and this number can be developed  in future by exploiting some other features in constructing watermark number other than SVD process to construct two watermark numbers, each one of them owned special methodology, for avoiding some challenges and changings in the transformation process.